The effects of low- and high-glycemic index meals on time trial performance - Moore, L. J. S.; Midgley, A. W.; Thomas, G.; Thurlow, S.; McNaughton, L. R. (International Journal of Sports Physiology and Performance, 2009)
Purpose: The aim of this work was to determine whether the consumption of preexercise high- or low-glycemic index (GI) meals has a beneficial effect on time trial performance. Methods: Eight male cyclists were provided with either a high-GI or low-GI meal, providing 1 g·kg-1 body mass of carbohydrate, 45 min before performing a 40-km time trial on a Velotron cyclePro. Results: Time trial performance was significantly improved in the low-GI trial (92.5 ± 5.2 min) compared with the high-GI trial (95.6 ± 6.0 min) (P = .009). Blood glucose concentrations at the point of exhaustion were significantly higher in the low-GI trial (5.2 ± 0.6 mmol·L-1) compared with the high-GI trial (4.7 ± 0.7 mmol·L-1) (P = .001). There was no significant difference in estimated carbohydrate oxidation data between the low-GI (2.51 ± 1.74 g·min-1) and high-GI (2.18 ± 1.53 g·min-1) meals (P = .195). No significant difference in estimated fat oxidation was observed between the low-GI (0.15 ± 0.15 g·min-1) and high-GI (0.29 ± 0.18 g·min-1) diets (P = .83). Conclusions: The improvement in time trial performance for the low-GI trial may be associated with an increased availability of glucose to the working muscles, contributing additional carbohydrate for oxidation and possibly sparing limited muscle and liver glycogen stores.